Morphological bases of ventricular arrhythmias in patients with chronic ischemic heart disease - Anton S. Shapkin (Kazimierz Wielki University, 2015)
Shapkin A. S. Морфологические основы желудочковых нарушений ритма при хронической ишемической болезни сердца = Morphological bases of ventricular arrhythmias in patients with chronic ischemic heart disease. Journal of Education, Health and Sport. 2015;5(6):131-140. ISSN 2391-8306. DOI 10.5281/zenodo.18417 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A131-140 https://pbn.nauka.gov.pl/works/564459 http://dx.doi.org/10.5281/zenodo.18417 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015.   МОРФОЛОГИЧЕСКИЕ ОСНОВЫ ЖЕЛУДОЧКОВЫХ НАРУШЕНИЙ РИТМА ПРИ ХРОНИЧЕСКОЙ ИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА   MORPHOLOGICAL BASES OF VENTRICULAR ARRHYTHMIAS IN PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE   А. С. Шапкин A. S. Shapkin   Харьковский национальный медицинский университет Kharkiv National Medical University   Abstract. This article presents pathomorphological changes of the atrioventricular part of the conducting system of the heart in patients with chronic ischemic heart disease followed by comparison of the results with the data electrocardiographic studies. It was noted that sclerotic, dyscirculatory and degenerative processes occurred in the structure of the conducting system that create conditions for the local delay of impulse conduction and formation of ectopic foci of excitation. The development of chronic blockades and delays of conduction accompanied by rough disorganization of the connective tissue carcass of the atrioventricular part of the conducting system of the heart and fibrous rings of the heart valves with compression and atrophy of muscle fibers. Acutely occurring blockades associated with hemorrhages in the region of the main structures of the conducting system of the heart. Keywords: conducting system of the heart, ischemic heart disease, arrhythmias.   Резюме. Проведено исследование патоморфологических изменений атриовентрикулярного отдела проводящей системы сердца у больных хронической ишемической болезнью сердца, с последующим сопоставлением полученных результатов с данными электрокардиографических исследований. Отмечено, что в структурах проводящей системы наблюдаются склеротические, дисциркуляторные и дистрофические процессы, создающие предпосылки для локальной задержки проведения импульса и формирования эктопических очагов возбуждения. Развитие хронически протекающих блокад и задержек проведения сопровождается грубой дезорганизацией соединительнотканного каркаса атриовентрикулярного отдела проводящей системы сердца и фиброзных колец клапанов сердца, со сдавлением и атрофией мышечных волокон. Остро возникающие блокады связаны с кровоизлияниями в области расположения основных структур проводящей системы сердца. Ключевые слова: проводящая система сердца, ишемическая болезнь сердца, аритмии.   Резюме. Проведено дослідження патоморфологічних змін атріовентрикулярного відділу провідної системи серця у хворих на хронічну ішемічну хворобу серця, з подальшим зіставленням отриманих результатів з даними електрокардіографічних досліджень. Відзначено, що в структурах провідної системи спостерігаються склеротичні, дисциркуляторні і дистрофічні процеси, що створюють передумови для локальної затримки проведення імпульсу і формування ектопічних вогнищ збудження. Хронічні блокади і затримки проведення супроводжується грубою дезорганізацією сполучнотканинного каркасу атріовентрикулярного відділу провідної системи і фіброзних кілець клапанів серця, що призводить до здавлення і атрофії м'язових волокон. Гостро виникаючі блокади супроводжуються крововиливами в основні структури провідної системи серця. Ключові слова: провідна система серця, ішемічна хвороба серця, аритмії.